2014
DOI: 10.4103/1305-7456.137647
|View full text |Cite
|
Sign up to set email alerts
|

The reparability of contemporary composite resins

Abstract: Objective:The objective was to investigate the way that various surface treatments could influence the bond strength of the repair of methacrylate (MC) and silorane (SIL) composites.Materials and Methods:A total of 160 MC and SIL cylindrical specimens were polymerized and aged in artificial saliva solution for 7 days. Depending on the following surface treatment (diamond bur or air abrasion), and the conditioning procedure (orthophosphoric acid or sodium hypochlorite), 16 groups were formed and repaired either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…Different commercial brands have different compositions, and the type of resin seems to be the main factor influencing the bond strength of the repair 3. However, it is noted that the practice of associating composite resins of different compositions is common during the restoration procedure 4.…”
Section: Introductionmentioning
confidence: 99%
“…Different commercial brands have different compositions, and the type of resin seems to be the main factor influencing the bond strength of the repair 3. However, it is noted that the practice of associating composite resins of different compositions is common during the restoration procedure 4.…”
Section: Introductionmentioning
confidence: 99%
“…27 Rodrigues et al 27 observed that the differences in the microstructure of resin composite influence average bond strength values and a nanoparticle composite resin displays an inferior bond strength compared with microhybrid composite resin. 28 Spyrou et al 28 observed differences in repair strength of composites based on different resin compositions.…”
Section: Discussionmentioning
confidence: 99%
“…When repairing the existing composite restoration, it is first necessary to prepare its surface mechanically to remove the outer layer of the aged composite that is most affected by saliva or other media, and to create an appropriate surface morphology for micromechanical bonding [23,45]. The composite surface is most commonly treated by grinding or air abrasion [7][8][9][10][11][12][13][14][15][16][17][19][20][21][22], or by the use of the Co-jet technique [9][10][11]18,20,[46][47][48][49] followed by the application of low-viscosity intermediate agents, usually enamel-dentin adhesive systems. In some papers, the silanization of the filler particles on the surface of the repaired composite is used [10,11,15,18,[20][21][22]29,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Surface treatment therefore plays a key role in the repair of composite restorations. The surface of the restoration is most often mechanically treated using a diamond bur and air abrasion [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Such treatments remove the aged surface layer of the existing composite restoration and create irregularities, which increase the surface wettability, roughness and total surface area [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation